2019
DOI: 10.1111/cen.14045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and depression score response after parathyroidectomy in primary hyperparathyroidism

Abstract: Objective Several studies indicate that patients with primary hyperparathyroidism (PHPT) undergoing parathyroid surgery have improvement in mood and neuropsychological functioning. The current analysis aims to examine the relationship between biochemical and clinical variables and the improvement in depression scores and in specific symptoms, after parathyroidectomy. Design A prospective observational case‐control study at a referral centre. Patients Patients with PHPT undergoing parathyroidectomy (n = 88) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
(102 reference statements)
1
22
0
Order By: Relevance
“…4 Parathyroidectomy in patients with HPT has shown to improve depression scores regardless of the biochemical severity of HPT. 5 In our case, we see an initial improvement in depressive symptoms after starting ECT, and further improvement after parathyroidectomy and continuing ECT. Regardless of the possible effect of parathyroidectomy on Mrs D's mood, ECT seems to have been effective in reducing depressive symptoms.…”
Section: Yokoyama Et Al Illustrate the Striking Psychopathological Si...supporting
confidence: 55%
See 1 more Smart Citation
“…4 Parathyroidectomy in patients with HPT has shown to improve depression scores regardless of the biochemical severity of HPT. 5 In our case, we see an initial improvement in depressive symptoms after starting ECT, and further improvement after parathyroidectomy and continuing ECT. Regardless of the possible effect of parathyroidectomy on Mrs D's mood, ECT seems to have been effective in reducing depressive symptoms.…”
Section: Yokoyama Et Al Illustrate the Striking Psychopathological Si...supporting
confidence: 55%
“…Neurocognitive symptoms are common in HPT and include anxiety, poor concentration, and cognitive decline 4 . Parathyroidectomy in patients with HPT has shown to improve depression scores regardless of the biochemical severity of HPT 5 . In our case, we see an initial improvement in depressive symptoms after starting ECT, and further improvement after parathyroidectomy and continuing ECT.…”
Section: Discussionmentioning
confidence: 49%
“…On the other hand, the inappropriate increase in PTH in patients affected by Primary Hyperparathyroidism (PHPT) [82,83] is correlated with a variety of neuropsychological symptoms, ranging from depression, anxiety, and sleeping disorders to dementia, psychosis, and cognitive decline [84]. Most neuropsychological symptoms are described in symptomatic PHPT, which is generally related to severe hypercalcemia, but they are also present in asymptomatic PHPT, with a prevalence of up to 60% of patients in some settings [85,86]. Prospective case-control studies have shown cognitive impairment, reduction in verbal and non-verbal memory, and a deficit of attention and semantic fluency, as evaluated by specific neuropsychological tests [87,88].…”
Section: Pth and Brain: Evidence From Clinical Settingsmentioning
confidence: 99%
“…(146) Most of them are described only in severe PHPT; their prevalence ranges from 3% to 50%. (7,19,(136)(137)(138)(151)(152)(153) In patients not complaining of these features, specific questionnaires have yielded a high prevalence (18%-61%) of neuropsychiatric issues and cognitive impairment in some studies. (140,152,(153)(154)(155)(156)(157)(158)(159)(160) Depression, anxiety, suicidal ideation, impaired memory, and disturbances in attention and executive function were most frequently reported.…”
Section: Neuromuscular Complicationsmentioning
confidence: 99%